Der p 1 Disrupts the Epithelial Barrier and Induces IL-6 Production in Patients With House Dust Mite Allergic Rhinitis - Ogi, Kazuhiro; Ramezanpour, Mahnaz; Liu, Sha; Ferdoush Tuli, Jannatul; Bennett, Catherine; Suzuki, Masanobu; Fujieda, Shigeharu; Psaltis, Alkis James; Wormald, Peter-John; Vreugde, Sarah (Frontiers in Allergy, 2021)
Background: Dermatophagoides pteronyssinus 1/2 (Der p 1/Der p 2) are regarded as important allergens of house dust mite (HDM). However, the effect of both products on the epithelial barrier and immune response of patients with and without HDM allergic rhinitis (AR) remains unclear. Methods: Air- liquid interface (ALI) cultured human nasal epithelial cells (HNECs) derived from control subjects (non-AR) (n=9) and HDM-AR patients (n=9) were treated with Der P 1 and Der P 2, followed by testing the transepithelial electrical resistance (TEER), paracellular permeability of fluorescein isothiocyanate (FITC)-dextran and immunofluorescence of claudin-1 and ZO-1. Interleukin-6 (IL-6) production was evaluated by ELISA. Results: Der p 1 reduced TEER significantly in a transient and dose-dependent manner in HNEC-ALI cultures from HDM-AR and non-AR patients, whilst the paracellular permeability was not affected. TEER was significantly reduced by Der p 1 at the 10-minute time point in HDM-AR patients compared to non-AR patients (p=0.0259). Compared to no-treatment control, in HNECs derived from HDM-AR patients, Der p 1 significantly cleaved claudin-1 after 30 minutes exposure (72.7±9.5 % in non-AR group, 39.9±7.1 % in HDM-AR group, p=0.0286) and induced IL-6 secretion (p=0.0271). Conclusions: Our results suggest that patients with HDM-AR are more sensitive to Der p 1 than non-AR patients with increased effects of Der p1 on the mucosal barrier and induction of inflammation, indicating an important role for Der p1 in sensitization and HDM-AR development.